LA CRAVATE ET LA MONTRE SEBUAH KALIGRAM KARYA APOLLINAIRE : ANALISIS SEMIOTIK - Armini, Alice (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2006)
rpieces remain timeless and his influence on the world of literature and artare greatly felt. The way typographical poetry, which is a kind of visual poetry orcalligram, is presented is extremely interesting and this article intends to describethe relation between the meaning of the words in the calligram and its pictorialform in one of Apollinaire's poems in the form of a calligram titled